2010
DOI: 10.1111/j.1365-2133.2010.09918.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray analyses demonstrate phosphate-bound gadolinium in skin in nephrogenic systemic fibrosis

Abstract: Background Nephrogenic systemic fibrosis (NSF) is an incurable, debilitating disease found exclusively in patients with decreased kidney function and comprises a fibrosing disorder of the skin and systemic tissues. The disease is associated with exposure to Gadolinium based contrast agents (GBCA) used in magnetic resonance imaging (MRI). Tissue samples from many NSF patients contain micron-sized insoluble Gd-containing deposits. However, the precise composition and chemical nature of these particles is unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 16 publications
4
51
0
Order By: Relevance
“…The question of which Gd species is actually involved in the pathogenesis of the lesions observed remains unanswered. Several studies have demonstrated micron‐sized insoluble deposits containing Gd associated with calcium and phosphate in NSF patients (Thakral and Abraham, 2009; George et al ., 2010). The protocol used in our study was unable to distinguish precipitated insoluble Gd in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The question of which Gd species is actually involved in the pathogenesis of the lesions observed remains unanswered. Several studies have demonstrated micron‐sized insoluble deposits containing Gd associated with calcium and phosphate in NSF patients (Thakral and Abraham, 2009; George et al ., 2010). The protocol used in our study was unable to distinguish precipitated insoluble Gd in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…injection, not interacting with substances in the body and being completely eliminated via the kidneys in unchanged form. However, ever since nephrogenic systemic fibrosis (NSF) in patients with advanced renal insufficiency (10,11) was linked to prior systemic administration of GdCM (12,13), the stability of GdCM complexes (14,15) and a possible release of Gd 3+ ions under certain circumstances have been subject to intensive investigation in both experimental (16)(17)(18)(19)(20) and clinical studies (21)(22)(23)(24)(25). NSF is altogether very rare with fewer than 500 cases registered by The International Center for Nephrogenic Systemic Fibrosis Research (26).…”
Section: Introductionmentioning
confidence: 99%
“…For a sample and reference geometry as shown in Fig. 4, and assuming a narrow beam such that the dimensions of the beam are much smaller than distance between the sample and the detector, then the equation for the sample or reference measurement is given by (5): detector solid angle, detection response, X-ray incident angle, X-ray incident energy, beam spot size, and material path lengths for both the sample and the reference measurements.…”
Section: Smooth Constant Thickness Homogeneous and Moderately Intementioning
confidence: 99%
“…To obtain further insight or to maintain biological or medical relevance quantifying these localized elemental concentrations is becoming increasingly important [2][3][4][5][6]. Traditionally XRF has been combined with quantification methods such as inductively coupled plasma mass spectrometry (ICP-MS) [7] and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) [8].…”
Section: Introductionmentioning
confidence: 99%